Factors affecting powerlifting performance: an analysis of age- and weight-based determinants of relative strength. (4th July 2018) - Latella, Christopher; Van den Hoek, Daniel; Teo, Wei-Peng
ABSTRACT: Powerlifting (PL) is characterised by the ability to generate maximal force. However, an understanding of the factors affecting strength in PL athletes is poorly understood. Therefore, competition data were analysed from 1368 individuals during 2017. Relative strength was compared for the squat (SQ), bench press (BP) and deadlift (DL) between age groups (Sub-junior [SJ], Junior [JU], Open [OP], and Masters' I-IV [M1-M4]), weight classes (females; 47 kg, 52 kg, 57 kg, 63 kg, 72 kg, 84 kg and + 84 kg and males; 59 kg, 66 kg, 74 kg, 83 kg, 93 kg, 105 kg, 120 kg, + 120 kg) and between sexes. The results showed that relative strength was greater for males across all lifts ( P  < 0.001). Relative strength tended to decrease with increasing body mass for males (SQ, BP and DL: P  < 0.001, R 2  = 0.9306–0.9763) and females (SQ, BP and DL: P  < 0.001, R 2  = 0.9485–0.9802), and with increasing age for males (SQ, BP and DL: P  < 0.001, R 2  = 0.4742–0.6729), and females (SQ: P  < 0.001, BP: P  = 0.002 and DL: P  = 0.001, R 2  = 0.0844–0.3705), respectively. The findings offer important information regarding factors that affect strength performance in athletes. Coaches should consider the factors influencing strength when developing resistance training programmes or in longer term athletic development for powerlifters and other strength based sports.